The Relationship Between Compensation and Job Satisfaction - Amiruddin, Nurin; Rodzalan , Shazaitul (Universitas Muhammadiyah Yogyakarta, 2022)
The intensifying economic competition makes every organization strive to increase its competitiveness in order to sustain in business environment. The success of an organization depends on the job satisfaction of the employees in the organization. However, job dissatisfaction occurs due to the salary received. Therefore, compensation is considered as something that can make employees satisfied with their jobs. This study aims to identify the level of compensation as well as the level of job satisfaction among manufacturing employees. In addition, this study also aims to identify the relationship between compensation and job satisfaction. Quantitative methods using questionnaires was used in this study. Primary data was distributed to a total sample of 375 employees in manufacturing companies in Johor Bahru. SPSS software was used to analyze the respondents' data. The results showed that the compensation that manufacturing employees received satisfied them. This study supports the hypothesis that there is a positive relationship between compensation and job satisfaction among manufacturing employees. This study benefits employees; if salaries are paid appropriately, employees will continue to meet the next level of need. This study can also help employers to improve compensation strategies in accordance with employee satisfaction. In addition, the government should plan a compensation package as employees play an important role in driving the Malaysian economy.